1997
DOI: 10.2307/3237033
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll fluorescence, stress and survival in populations of Mediterranean grassland species

Abstract: Abstract. Photosynthetic stress in response to a natural episode of frost and seasonal drought was assessed in a ‘dehesa’ grassland of SW Spain with a portable fluorimeter. Chlorophyll fluorescence characteristics of dark‐adapted leaves of 11 abundant species of Mediterranean grassland were measured over the course of a growing season from November 1992 to July 1993. Concomitant changes in population size were estimated from censuses of permanent quadrats. There was a general decline in the photochemical effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 32 publications
(36 reference statements)
4
24
0
Order By: Relevance
“…A fluorescence meter emits light at 680 nm and after 10 s of exposure, a reading is taken to measure the 695 nm light energy being re-emitted by the plant (Fv/Fm). This provides a relative measure of vigor because photosystem II quantum efficiency is a reliable indicator of plant stress (Figueroa et al 1997). For analysis, Fv/Fm values were regressed on time for each seed source-salinity combination.…”
Section: Greenhouse Salinity Tolerance Experimentsmentioning
confidence: 99%
“…A fluorescence meter emits light at 680 nm and after 10 s of exposure, a reading is taken to measure the 695 nm light energy being re-emitted by the plant (Fv/Fm). This provides a relative measure of vigor because photosystem II quantum efficiency is a reliable indicator of plant stress (Figueroa et al 1997). For analysis, Fv/Fm values were regressed on time for each seed source-salinity combination.…”
Section: Greenhouse Salinity Tolerance Experimentsmentioning
confidence: 99%
“…High F 0 values are only recorded in July, with maximum records at 14:00, that is, coincidentally with the lowest T m values, particularly in the case of Helianthemum squamatum and, to a lesser extent, in the case of Gypsophila struthium. This would indicate some damage in the plant photosystems induced by exposure to light (Figueroa et al, 1997). However, this damage is by no means long-lasting, since the F v /F m values return to normal levels during the night in the three species.…”
Section: Discussionmentioning
confidence: 92%
“…The recording of chlorophyll fluorescence values is a useful method for checking PSII photosynthetic efficiency and, therefore, the plant photosynthetic response to environmen-tal disruptions (Figueroa et al, 1997). With the introduction of easy-to-handle, portable fluorimeters capable of providing a large amount of data with only a minimum of experience and time on the part of the researcher, and without damaging the plants, it is nowadays relatively easy to record in the field the fluorescence kinetic values induced by quick exposure to actinic light in leaves previously adapted to darkness.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of chlorophyll content and fluorescence has become established as a sensitive method for assessing the efficiency of PSII photosynthetically, as well as its role in environmental perturbations of photosynthesis. Some researchers have reported that chlorophyll content might estimate the influence of environmental stress on growth because these parameters were closely correlated with the rate of carbon exchange (Figueroa et al 1997;Guo and Li 2000).…”
Section: Resultsmentioning
confidence: 99%